Study of the Power Output of a Thermoelectric Generator (TEG) Prototype in Utilizing Asphalt Heat through Variations in Copper Plate Thickness as a Heat Conductor - Ike Bayusari; Anggun Ismeriyanti Putri; Ayu Soraya; Caroline; Hermawati; Rahmawati (Politeknik Negeri Sriwijaya, Indonesia, 2026)
Asphalt, as a key infrastructure element, absorbs solar heat and can be utilized as a renewable energy source through Thermoelectric Generator (TEG) technology, which converts temperature differences into electrical energy. This study evaluates the performance of a TEG system equipped with copper plates high thermal conductivity heat conductors with varying thicknesses of 1 mm, 2 mm, and 3 mm. The highest average values of ∆T, voltage, current, and output power for the 1 mm copper plate were 6.12 °C, 349 mV, 2.973 A, and 1037.58 mW, respectively. For the 2 mm plate, the values were 7.39 °C, 294 mV, 3.196 mA, and 939.62 mW, while the 3 mm plate yielded 7.56 °C, 363 mV, 1.928 A, and 699.86 mW. The results suggest that the 2 mm copper plate provides the most optimal configuration to enhance TEG performance without inducing excessive thermal resistance, thereby delivering the highest overall current and power output.